AN ANALYSIS ON THE RELATIONSHIP BETWEEN THE PEDAGOGİCAL AND MATHEMATICAL CONTENT KNOWLEDGE OF MATHEMATICS TEACHERS - Yasin SOYLU (Fırat University, 2019)
Nowadays, considerable changes are taking place within mathematics education as to what mathematics is and how it should be taught. With the changing perspective in education, a shift has occurred from conveying the existing knowledge to showing ways to reach educational knowledge in teacher-student relationships. Therefore, well-trained teachers play a crucial role in the education system. The purpose of this study is to determine the relationship between mathematics teachers’ pedagogical content knowledge and mathematical content knowledge. 41 mathematics teachers took part in this study and the qualitative research design was applied. In this framework, eight open-ended questions were asked for data gathering purposes. Data was gathered from semi-structured interviews and teachers' written explanations. The content and descriptive analysis method was used for data analysis. According to the data, there was a relationship between teachers’ mathematical content knowledge and pedagogical content knowledge. The results of the study showed that most of the teachers’ knowledge of mathematics was inadequate for teaching mathematics in some areas and that teachers’ instructional explanations were in the form of a restatement of the procedures. It was concluded that few teachers’ instructional explanations about some mathematics statements were at a conceptual (content, epistemic or problem-solving levels) level and most of the teachers’ of mathematics content knowledge at this level was correct.